3D-Printing of paracetamol tablets by fused deposition modelling - Pereira, Gabriela G. (2022)
Abstract of poster presented at the 12th PBP World Meeting on Pharmaceutics, Biopharmaceutics and Pharmaceutical Technology, Wien, Austria, 11-14 May 2021 (virtual Meeting)